2002
DOI: 10.1207/s15327965pli1304_01
|View full text |Cite
|
Sign up to set email alerts
|

TARGET ARTICLE: Hope Theory: Rainbows in the Mind

Abstract: Vannette, D. (2017). Using attention checks in your surveys may harm data quality. https://www.qualtrics.com/blog/using-attention-checks-in-yoursurveys-may-harm-data-quality/ Van Orden, K. A., Cukrowicz, K. C., Witte, T. K., & Joiner, T. E. ( 2012).Thwarted belongingness and perceived burdensomeness: Construct validity and psychometric properties of the Interpersonal Needs Questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

105
2,803
9
201

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,733 publications
(3,118 citation statements)
references
References 119 publications
105
2,803
9
201
Order By: Relevance
“…Crowd-powered technologies could intervene in at least two cognitive components believed to be important for healthy goal pursuit -"pathways thinking" and "agency thinking" (Snyder, 2002). Pathways thinking, as described by Snyder (2002), is the process of identifying the specific routes and steps needed to attain a goal. Crowds could be recruited to help users define clear blueprints for goal attainment.…”
Section: Goal Setting and Planningmentioning
confidence: 99%
“…Crowd-powered technologies could intervene in at least two cognitive components believed to be important for healthy goal pursuit -"pathways thinking" and "agency thinking" (Snyder, 2002). Pathways thinking, as described by Snyder (2002), is the process of identifying the specific routes and steps needed to attain a goal. Crowds could be recruited to help users define clear blueprints for goal attainment.…”
Section: Goal Setting and Planningmentioning
confidence: 99%
“…Feelings of hope related to climate change, for example, likely increase the probability that individuals will choose to engage with the issue and adopt beliefs and behaviors consistent with efforts to stem the problem (Markowitz and Shariff 2012;Snyder 2002;Swim et al 2010). Hope is often aroused as perceptions of efficacy, the belief that an individual has the capacity to implement a proposed response to a threat and that the recommended action can effectively mitigate the threat, increase (Bandura 1977).…”
mentioning
confidence: 99%
“…In other domains, research has shown that hope in both its trait and state forms is an effective predictor of various performance-related behaviors (Snyder, 2002). More specifically, previous studies demonstrated that trait hope predicted performance and grade either directly (e.g., Marques et al, 2011; or indirectly (Curry et al, 1997;Peterson et al, 2006), through state hope.…”
Section: The Present Studymentioning
confidence: 99%